Prototype of totally solid Rechargeable Lithium Ion Microbacteria based on Thin Films produced by High Vacuum techniques - Ponce, Bertha (2005)
In this paper we report the production of a prototype of all-solid rechargeable ion-lithium microbatteries based on thin films produced by de and rf magnetron sputtering techniques. The anode is made of Li Al films, the electrolyte is made of an amorphous film of lithium phosphorus oxynitride (LiPON), the cathode is a film of lithium cobalt oxide (Li Coo). Besides the production process for the different components and the battery itself, here we report the characterization of the LiPON films by UV/Visible spectrophotometry and infrared spectrometry, as well, the characterization of Li CoO, by infrared spectrometry.